The Effect of Salt Solutions and Absorption Cycles in the Capillary and Drying Coefficient of Red Brick Samples with Different Joints - A. S. Guimarães; J. M. P. Q. Delgado; V. P. de Freitas; A. P. Albuquerque (Advances in Materials Science and Engineering)
Rising damp can reduce building’s aesthetical value, comfort, and health mark when combined with the existence of soluble salts in the building components and in the ground water can even lead to material decomposition and compromise its structural performance. This research work intended to study the effect of different absorption cycles of two saturated solutions of sodium sulphate and potassium chloride in the capillary absorption curves obtained through the partial immersion of red brick samples without and with different joints. The results revealed significant differences in the capillary coefficients obtained when samples were tested with salt solutions. In the end of this paper an evaluation of the drying kinetics was presented for all the tested samples. Four different first-order kinetics models, available in the literature, were adjusted to describe the drying process and the results point that the Page and Logarithmic models allow the best fit. The apparent molecular diffusion coefficient for solid red brick samples saturated with different solutions and joints was also estimated.